Effect of maternal supplementation with vitamin E on the concentration of α‐tocopherol in colostrum - Larisse Rayanne Miranda de Melo; Heleni Aires Clemente; Dalila Fernandes Bezerra; Raquel Costa Silva Dantas; Héryka Myrna Maia Ramalho; Roberto Dimenstein (Brazilian Society of Pediatrics, 2017)
Objective: To evaluate the effect of maternal supplementation with vitamin E on the concentration of α‐tocopherol in colostrum and its supply to the newborn. Method: This randomized clinical trial enrolled 99 healthy adult pregnant women; of these, 39 were assigned to the control group and 60 to the supplemented group. After an overnight fast, 5 mL of blood and 2 mL of colostrum were collected. After the first sampling (0 h milk), the supplemented group received 400 IU of supplementary vitamin E. Another 2 mL milk aliquot was collected in both groups 24 h after supplementation (24 h milk). The samples were analyzed by high‐performance liquid chromatography. The α‐tocopherol content provided by colostrum was calculated by considering a daily intake of 396 mL of milk and comparing the resulting value to the recommended daily intake for infants aged 0-6 months (4 mg/day). Results: The initial mean concentration of α‐tocopherol in colostrum was 1509.3 ± 793.7 μg/dL in the control group and 1452.9 ± 808.6 μg/dL in the supplemented group. After 24 h, the mean α‐tocopherol concentration was 1650.6 ± 968.7 μg/dL in the control group (p > 0.05) and 2346.9 ± 1203.2 μg/dL in the supplemented group (p < 0.001), increasing the vitamin E supply to the newborn to 9.3 mg/day. Initially, 18 women in the supplemented group provided colostrum α‐tocopherol contents below 4 mg/day; after supplementation only six continued to provide less than the recommended amount. Conclusion: Maternal vitamin E supplementation increases the supply of the vitamin to the infant by providing more than twice the Recommended Daily Intake.